Realization of two-dimensional spin-orbit coupling for Bose-Einstein condensates - Wu, Zhan; Zhang, Long; Sun, Wei; Xu, Xiao-Tian; Wang, Bao-Zong; Ji, Si-Cong; Deng, Youjin; Chen, Shuai; Liu, Xiong-Jun; Pan, Jian-Wei (Science (American Association for the Advancement of Science), 2016)
Cold atoms with laser-induced spin-orbit (SO) interactions provide a platform to explore quantum physics beyond natural conditions of solids. Here we propose and experimentally realize two-dimensional (2D) SO coupling and topological bands for a rubidium-87 degenerate gas through an optical Raman lattice, without phase-locking or fine-tuning of optical potentials. A controllable crossover between 2D and 1D SO couplings is studied, and the SO effects and nontrivial band topology are observed by measuring the atomic cloud distribution and spin texture in momentum space. Our realization of 2D SO coupling with advantages of small heating and topological stability opens a broad avenue in cold atoms to study exotic quantum phases, including topological superfluids.